El cuento y la dramatización como estrategia en el proceso de enseñanza-aprendizaje en los niños y niñas de educación inicial y primer año de la escuela de educación general básica 24 de Julio y Eugenio Espejo de la ciudad de Machala parroquia Puerto Bolívar en el periodo lectivo 2012-2013. - Illescas Cely, Deayse Beatriz (2013)
This research work has developed during this time is very important because through research process has been very rewarding to implement it in professional life, in which the beneficiaries will be children of pre-school and first year of basic education as it is to them that this work is directed the responsibility of all teachers in pre-school is to make a fun class in every sense of the word, giving the opportunity for boys and girls to get involved in daily activities, so that learning is meaningful and remain embodied the putting skills into practice in everyday life to solve the various problems they encounter and freely express their emotions and spontaneity and feeling that can put them in different ways.